Efektivitas Multimedia IPA berbasis Kearifan Lokal Keris (M-Keris) terhadap Pemahaman Konsep Siswa - Dolo, Fransiskus Xaverius; Prodjosantoso, A.K. (Jurnal Pendidikan Indonesia, 2022)
Lack of understanding of students' concepts of science material. This study aims to improve students' conceptual understanding using multimedia based on local wisdom of the keris. This type of research is a quasi-experimental design using a nonequivalent control group design technique. The population in this study were class VII students, which were divided into experimental class and control class. The data collection instrument was in the form of a concept understanding test. The data analysis technique used independent sample t-test analysis. The results showed that there were differences in the effectiveness between M-Keris and conventional Multimedia on understanding the concepts of class VII students. Based on the results of the analysis which shows the value of Sig. (2-tailed) in the independent sample t test was 0.018 < 0.05. The role of multimedia elements contained in M-Keris is an important factor to build interest in learning and students' understanding of the concepts presented. Therefore, learning with M-Keris is more effective and makes it easier for students to understand the concepts given compared to other conventional multimedia. In addition, with M-Keris, the teacher's function will be fully as a facilitator who directs and helps students explain things that have not been understood. The implication of this research is that teachers are expected to be able to use M-keris in the learning process. So as to improve student learning outcomes.